Keadaan Ibu Hamil Dengan Diabetes Melitus Di PUSKESMAS Tuntungan Tahun 2020-2021 - Rahmawani Fauza (Journal of Health and Medical Science, 2022)
Diabetes does not only affect the old age group, but has shifted to the young and productive age group, including pregnant women. Under normal conditions, blood sugar levels in the body are regulated by the hormone insulin. Most maternal deaths are known to be caused by other causes that are not detailed and the exact cause is known (63 people), due to bleeding (67 people), due to hypertension (51 people), due to infection (8 people), due to circulatory system disorders ( 8 people), as well as due to metabolic disorders (5 people). The purpose of this study was to determine the condition of pregnant women with a history of diabetes mellitus. The method in the study of pregnant women with a history of diabetes mellitus at the Tuntungan Health Center in 2020-2021 was descriptive quantitative, by collecting data from medical records at the Tuntungan Health Center and collected as many as 20 mothers with diabetes mellitus. The entire population was taken for the sample in this study. In the study of pregnant women with Diabetes Mellitus at the Tuntungan Health Center, the average effect on maternal age, mother's education, mother's weight, mother's condition with a family history of Diabetes Mellitus, and maternal glycosuria. From the results of this study, researchers have suggestions for health centers to provide health education to pregnant women who have diabetes to check their health regularly, and provide health education so that their diabetes does not get worse.